High throughput profiling of the B cell repertoire identifies systematic changes in the repertoire of individuals with Crohn’s disease - Mahdy, Aya K. H.; Taheri, Zahra; Høivik, Marte Lie; Franke, Andre; ElAbd, Hesham (Frontiers in Immunology, 2026)
The B cell repertoire contains the recombined sequences that encode the entire antibody repertoire of an individual. The repertoire is made from three antigenic binding chains, namely the immunoglobulin heavy chain (IGH) and two immunoglobulin light chains, κ (IGK) and λ (IGL). Compared to the T cell repertoire, the B cell repertoire is understudied in inflammatory bowel diseases (IBD) even though different antibodies such as ASCA (Anti-Saccharomyces cerevisiae) and ANCA (Anti-Neutrophil Cytoplasmic Antibodies) have been shown to be elevated in individuals with IBD. To address this limitation, we profiled the B cell repertoire of peripheral blood from 27 treatment-naive individuals with CD and 21 age-matched symptomatic controls using bulk B cell receptor sequencing. The repertoire of individuals with CD showed a reduction in diversity and an increase in clonality. Furthermore, we observed a significant reduction in the expansion of IgM and IgD and an expansion of IgA2, and IgG2 clonotypes in individuals with CD relative to controls, suggesting an antigen-driven expansion. This was also supported by higher levels of somatic hypermutations, particularly in the complementary determining region 2 (CDR2) of immunoglobulin heavy chain, in individuals with CD relative to the control group. Thus, despite the small sample size, we identified multiple alterations in the B cell repertoire of individuals with CD, highlighting the potential of the B cell repertoire in identifying antigenic exposures implicated in the disease, demanding now larger international studies, ideally including also treatment-naive and pre-clinical cases.